What did the European Community founders actually mean by saying that the treaties shall in no way prejudice the rules in member states governing the system of property ownership? Analysis of Article 345 TFEU - Mataczyński, Maciej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis of the Article 345 of the Treaty on the Functioning of the European Union. The author presents the relation between European Union law and the member state law regulating property ownership. The author makes an attempt to answer what did the European Community founders actually mean by the treaties shall in no way prejudice the rules in member states governing the system of property ownership.